2018
DOI: 10.1371/journal.ppat.1007368
|View full text |Cite
|
Sign up to set email alerts
|

An unusually high substitution rate in transplant-associated BK polyomavirus in vivo is further concentrated in HLA-C-bound viral peptides

Abstract: Infection with human BK polyomavirus, a small double-stranded DNA virus, potentially results in severe complications in immunocompromised patients. Here, we describe the in vivo variability and evolution of the BK polyomavirus by deep sequencing. Our data reveal the highest genomic evolutionary rate described in double-stranded DNA viruses, i.e., 10−3–10−5 substitutions per nucleotide site per year. High mutation rates in viruses allow their escape from immune surveillance and adaptation to new hosts. By combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 89 publications
(87 reference statements)
5
11
0
1
Order By: Relevance
“…S1 and S2). This rate also falls in line with those observed in other coronaviruses 25,26 and is fairly unremarkable relative to other positive single-stranded RNA viruses, which do not have a viral proof-reading mechanism 27,28 .…”
Section: Resultssupporting
confidence: 84%
“…S1 and S2). This rate also falls in line with those observed in other coronaviruses 25,26 and is fairly unremarkable relative to other positive single-stranded RNA viruses, which do not have a viral proof-reading mechanism 27,28 .…”
Section: Resultssupporting
confidence: 84%
“…We informally estimate the mutation rate over our alignment to 9.6 x 10 -4 substitutions per site per year, which is consistent with previous rates estimated for SARS-CoV-2 [1-4] ( Figure S1-S2). This rate also falls in line with those observed in other coronaviruses [24,25], and is fairly unremarkable relative to other positive single-stranded RNA viruses, which do not have a viral proof-reading mechanism [26,27]. Table S1.…”
Section: Global Diversity Of Sars-cov-2supporting
confidence: 83%
“…Among the proteins described in the present study, some contain domains typical for bacteriophages, but no direct homology was found. This is probably due to the fast evolutions of viral genomes [ 69 , 70 ] which can mask the similarity of related proteins [ 71 ]. Nevertheless, cysteine-rich repeats can serve as an instrument to find new cases of prokaryote to eukaryote HGT.…”
Section: Discussionmentioning
confidence: 99%